Strengthen the unified accounting system in rental sales Transactions to increase the protection of the real estate trade in installment Proposed framework - عبد الله سلمان حسين; مجيد محمد زهير (Journal of Economics and Administrative Sciences, 2017)
Due to the large size of dealing in the transactions installment sales in durable products, especially real estate given the privacy to enjoy their property, among other products because of the large amount and the length of the repayment period leading to a risk of non-payment by the buyer because of the possibility to change the credit level to him, especially that most of this type of transaction customers are from limited income owners, So it has been proposed the use of other transactions in handling real estate instead of installment sales transactions, a rental sale transactions because of the protection provided by this transaction for a vendor that will be mentioned later. So proposes to strengthen the Iraqi unified accounting system by adding the rules of measurement and special accounts that can be applied uniformly in Iraqi companies that working in real estate trade an installments, to makes this system more ability to provide accounting information and protection to the seller, because the accounting system applied in these units does not cover all types of transactions, including the installment sale and leasing of the service units of Iraq’s economic transactions.